The Level of Design Thinking Utilization Among History Teachers at the Secondary Stage (Journal of the College of Basic Education, 2026)
This study aimed to identify the level of design thinking utilization among history teachers at the secondary stage. To achieve the study objectives, the descriptive analytical method was adopted. The study sample consisted of 100 male and female teachers from various directorates in Al-Karkh, selected using stratified random sampling. A questionnaire comprising 30 items was prepared, distributed across three domains:)1-Theoretical knowledge of design thinking (10 items)2-Identification of design thinking (10 items)3- Implementation of design thinking (10 items) The psychometric properties of the tool were verified. The results showed the following levels of design thinking utilization:( Identification of design thinking ranked first with an achievement rate of 81%)( Implementation of design thinking ranked second with an achievement rate of 75%)( Theoretical knowledge of design thinking ranked third with an achievement rate of 68%) Regarding the second objective, which is to identify differences based on gender (male-female), the results indicated that there were no statistically significant differences in the level of design thinking utilization between genders.The researcher concluded several findings, including a lack of knowledge and awareness among history teachers regarding design thinking, which leads them to rely on traditional teaching methods. Among the recommendations was the need to promote design thinking-based teaching, as acquiring design thinking enhances students’ learning and academic achievement.